GLYCEMIC INDEX AND IMPACT OF FOOD FORMULATED FROM LOCALLY AVAILABLE STUFF ON PROTEIN STATUS OF MALNOURISH CHILDREN IN KANO, NIGERIA - Gadanya, A. M.; Abubakar, S. M.; Yahaya, A. S.; Sidan, A. A.; Muhammad, D.; Yarima, M. A. (FUDMA JOURNAL OF SCIENCES, 2023)
This research was carried out to study the effect of consumption of food formulated from locally available stuff on serum protein profile of malnourished children of Hasiya Bayero pediatric Hospital Kano State, Nigeria. Ethical approval was sought from the ethical committee of Ministry of health Kano. Males (10) and females (10) malnourished inpatient children aged 6-59months participated in the study. Food was formulated using sorghum (Sorghum arundinaceum), date (Phoenix dactylifera), groundnut (Arachis hypogaea), soybean (Glycine max) and moringa leaf (Moringa oleifera). The formulated food (300g) was given to each child per day and consumed for a period of 2 weeks. Appetite test and glycemic index of the food were determined. Serum total protein (TP), albumin (ALB) and globulin (GLO) were determined before (baseline) and 2 weeks after feeding. Glycemic index of the formulated food was found to be high of about 91.66mg/dl. Mean serum TP, ALB, and GLO levels of male children as well as mean serum GLO of female children volunteers were significantly increased (P
Keywords: Food formulation, local ingredients, protein status, malnourish children